PENGARUH KEPEMIMPINAN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI KANTOR POS INDONESIA SITINJAK - Kirana Agung M. Rahim; Nabila Hilmy Zhafira (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
This study aims to analyze partially and simultaneously between leadership in a company, and the compensation given by the company to the performance of Sitinjak POS office employees. This research method uses analysis to test the hypotheses. The respondents used in this study were 21 employees. Data collection was carried out by distributing questionnaires to the sample population using Google Forms with quantitative techniques and linear regression testing. Furthermore, the results obtained were processed using analysis using software called Statistical Product and Service Solution or abbreviated as (SPSS) version 25, and Microsoft Excel. Researchers get the result that the variables of leadership (X1) and compensation (X2) have a positive and significant effect. to the performance of the employees of the Sitinjak POS office, then simultaneously the leadership and compensation variables also have an influence on the performance of the employees of the Sitinjak POS Indonesia office with a value of 63.7 percent